A Colombian classic management thinker: Alejandro López Restrepo. Issue 2 (12th March 2019) - Orozco, Luis Antonio; Anzola-Morales, Olga Lucía
Abstract : Purpose: This paper aims to present the Colombian Alejandro López Restrepo as a classic management thinker from the first half of the twentieth century and discuss his ideas in the light of Anglo-Saxon authors at that time and his contributions as a professor, manager and public servant. Design/methodology/approach: Bibliographic material including López's books and essays and their biography published by Mayor (2001) are reviewed to organize a new reading of López as a management thinker and practitioner. Findings: Beyond several classical managerial thinkers, López reconceptualized scientific management with a critical discussion of classical economic theory using sociology and psychology to present a unique conception of work, enterprise and efficiency as a public service that gives sense to individual and social realization to face the future and create development. Research limitations/implications: Techniques as critical biography and interpretation of data have not been used, instead the aim to contribute to the literature of management history a Latin American' thinker. Practical implications: Including López as a classical management thinker can improve the study of management history. His life and ideas give new reflexive insight to understand the development of management in Colombia and serve to inspire administrators to seek improvements in society. Originality/value: The paper offers a new approach toward studying Alejandro López beyond previous sociological work by Mayor (2001) with the discussion of the contributions in the lenses of managerial practices and theoretical insights at that time.